Body weight regulation of a low molecular weight xanthan gum on normal mice via gut microbiota. (January 2022) - Sun, Xincheng; Zhao, Chengxin; Hu, Xuyang; Zhang, Jingnan; Xu, Suyue; Li, XiaYing; Bai, Yanhong; Zhang, Xiaogen; Hu, Jinqiang; Sun, Qi; Wang, Zichao
Graphical abstract: Highlights: LW-XG was safe to Caco-2 cells and normal mice. Body weight gain increased from 10.78 ± 2.15 g to 13.28 ± 1.97 g. LW-XG increased short-chain fatty acids (SCFAs) contents in the cecum of mice. LW-XG increased the abundance and diversity of gut microbiota. Firmicutes / Bacteroidetes ratio increased from 0.3547 to 1.5371. Abstract: Properties of thickening, emulsification and suspension make xanthan gum is widely used in foods and other industries, but effects of xanthan oligosaccharide or low molecular weight xanthan gum (LW-XG) on the nutrition of human body are rarely investigated. Presently, body weight regulation effect of a LW-XG on male mice was assayed. Results showed that LW-XG was safe to Caco-2 cells and mice, and increased mice body weight gain from 10.78 ± 2.15 g to 13.28 ± 1.97 g. Meanwhile, the acetate, propionate, butyrate and total short-chain fatty acids (SCFAs) contents increased from 25.13 ± 1.28 μmol/g, 11.28 ± 0.81 μmol/g, 7.85 ± 0.43 μmol/g and 44.26 ± 1.85 μmol/g to 41.76 ± 1.08 μmol/g, 19.84 ± 0.97 μmol/g, 12.58 ± 0.26 μmol/g and 74.18 ± 1.72 μmol/g, respectively. Furthermore, LW-XG increased the abundance and diversity of gut microbiota, and Firmicutes / Bacteroidetes ratio was significantly increased from 0.3547 to 1.5371.